Antiplasmodial Properties of Methanol Leaf Extract of Laggera aurita Linn in Experimental Animals - Magajia, Shehu Yakubu; Sani, Malami (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Laggera aurita Linn (Asteraceae) is ethnomedicinally used in the treatment of malaria, epilepsy, fever, pain, stomatitis, bronchitis, nasal congestion, asthma and bacterial infections. This research is aimed at evaluating the antiplasmodial activity of the plant in mice. The plant extract was evaluated using three in vivo antiplasmodial models in mice; 4-day suppressive, prophylactic and curative tests against chloroquine-sensitive Plasmodium berghei-berghei. Effects of the extract on blood glucose level and hematological indices in mice infected with P. berghei-berghei were also evaluated. Antipyretic effect of the extract was also studied in rats using Brewer’s yeast induced pyrexia. The extract exhibited significant (p<0.05) dose-dependent decrease in parasitaemia level in all the three models when compared to the control groups. The extract extended the mean survival of the mice beyond 21 days in a dose dependent manner. Also, the extract significantly (P<0.05) lowered blood glucose level with no significant (p<0.05) effect on hematological indices in mice infected with the parasite. In Brewer’s yeast-induced pyrexia test, the extract exhibited statistical significant (p<0.05) reduction of pyrexia in rats. Results of this study suggested that the methanol leaf extract of L. aurita possesses antiplasmodial and antipyretic activities. Therefore, the study lends scientific credence to the acclaimed ethnomedicinal use of the plant in the treatment of malaria.